Sport-related concussion: On-field and sideline assessment - Guskiewicz, K. M.; Broglio, S. P. (Physical Medicine & Rehabilitation Clinics of North America, 2011)
The careful and well-planned sideline assessment of concussion can be the difference between a good and bad outcome when managing sport-related concussion. In most cases, the sideline assessment serves as a triage for determining if an injury, such as a concussion, has actually occurred, and if so, establishes a benchmark for determining whether a more serious and potentially catastrophic condition could be developing. Concussions can evolve into something more serious if signs and symptoms go undetected or are ignored. Although these are very rare events, they must always be at the forefront of the clinician`s mind.